Handling the Covid-19 Outbreak in Review from the Legal Aspect: Penanganan Wabah Covid-19 di Tinjau dari Aspek Hukum - Raimon Efendi; Ratih Agustin Wulandari (Perkumpulan Doktor Indonesia Maju, 2022)
The abstract is to be in fully-justified italicized text, at the top of the paper with single column as it is here, below the author information. Use the word “Abstract” as the title, in 10-point Times, boldface type, left relative to the column, initially capitalized. The abstract is to be in 10-point, single-spaced type, and up to 200 words in length. Leave two blank lines after the abstract or list three to five keywords related to the articles, then continued with abstract in bahasa Indonesia.